The use of pain neuroscience education in older adults with chronic back and/or lower extremity pain. (3rd July 2019) - Rufa, Adam; Beissner, Katherine; Dolphin, Michelle
ABSTRACT: Introduction : Chronic pain due to musculoskeletal disorders is the leading cause of disability among older adults and is associated with a lower quality of life, reduced function, and increased risk of institutionalization. Pain Neuroscience Education (PNE) has demonstrated effectiveness in reducing pain and improving pain self-efficacy in individuals under 60 years of age, but there is a paucity of research examining its use with older adults. If PNE has similar effects in older adults, it has the potential to be a useful non-pharmacological intervention for this population.Methods : This quasi-experimental feasibility study included 25 subjects over the age of 65 with a 3 month or greater history of lower back and/or lower extremity pain. Subjects participated in two semi-standardized one-on-one PNE sessions and were asked to read a booklet (Why Do I Hurt, Louw, International Spine and Pain Institute, USA) in between sessions. Subjects' perception of PNE was measured after the second session and gait speed, pain disability, and fear of movement were measured pre- and post-PNE.Results : Subjects consistently reported a positive experience with PNE. There were statically significant positive improvements in gait speed, pain disability, and fear of movement after the intervention.Conclusion : PNE is a feasible and potentially efficacious treatment for older adults with chronic pain.